Hunter and Non-Hunter Perceptions of Costs, Benefits, and Likelihood of Outcomes of Prescribed Fire in the Mid-Atlantic Region. Issue 10 (2nd October 2020) - Miller, Zachary D.; Wu, Hong; Zipp, Katherine; Dems, Cody L.; Smithwick, Erica; Kaye, Margot; Newman, Peter; Zhao, Anthony; Taylor, Alan
Abstract: In the mid-Atlantic region, prescribed fire is as an important tool for natural resource managers to achieve a variety of outcomes, including the management of wildlife habitat and wildfire risk reduction. However, little research has been conducted in this region to help inform managers about public perceptions and acceptance of prescribed fire. In this research, data from intercept surveys of hunter and non-hunters on public lands in New Jersey and Pennsylvania are used to compare perceptions of perceived costs, benefits, and ikelihood of outcomes for these groups related to prescribed fire. Results show that hunters generally had lower levels of perceived costs and likelihood of negative outcomes from prescribed fire than non-hunters. From this, managers using prescribed fire in these areas can better understand public perceptions, differences among recreation users, and possibly better communicate about using prescribed fire as a tool for managing resources.